Cultural dynamics of child labour in Yobe State Nigeria - Ibrahim, Aisha Ningi; Talib, Ahmad Tarmizi; Paim, Laily; Gill, Sarjit S. (International Organization of Scientific Research, 2015)
The purpose of this paper is to provide a qualitative explanation of the cultural dynamics of the causes of child labour in Yobe state which is regarded as one of Nigeria’s educationally less developed states. The study is limited to the reasons for girls involvement in child labour (with specific attention to street hawking largely seen and regarded as another form of child labour). This will add to the growing literature on child labour in developing countries and also provides the policy makers with inclusive policies and programmes for girls development. The study described the socio-cultural setting of the State, the nature of street hawking prevalent among girls and the reasons for their engagement. The research design, methodology, and approach involved qualitative approach using case study which specifically focused on the girl hawkers in Yobe State, Nigeria. The state has 17 LGAs; however, this study focuses on Potiskum town the headquarters of the Potiskum Local Government Area. The selection criteria of Potiskum are informed not only by its heterogeneous nature, but because of its strategic location and being the economic nerve centre of the State. Data collection technique also involves participant observations, interviews, and focus group discussions using semi-structured openended questions. For data analysis, the observational data were converted to field notes and analysed, as well as interviews. The raw data were analysed using transcriptions, sorting, and repeated readings that identified major themes. Major findings were presented as themes under cultural, social, and economic motives for girls involvement in street hawking. The causes included means to girls socialization, exposing girls to suitors as future husbands, for family honour, to accrue income to maintain their bodily aesthetic needs, to finance wedding expenses, poverty level of most families, and to augment family income. Challenges facing the girls includes, exposure to all forms of abuse, being left behind in basic literacy, and lack of safety. Conclusively, this paper is of significant value due to its novelty because in Yobe State, as there has not been a detailed or comprehensive study on the motives for girls involvement in street hawking. As almost all existing study focused more on regional basis and the results are mainly from survey data. Also, previous researches tended to link the problem with poverty, but this study is suggesting that poverty alone cannot explain their presence on the streets. Therefore, it will serve as source of additional literature for those who have interest on human development and enhancing the status of the most vulnerable groups in our society. It will also be a good source of information to policy makers and other stakeholders about the situation in Yobe State where women voices are seldom heard.